Analysis of Profit-Sharing Financing Investment Ratio to Total Sharia Banks Financing in 2018 - 2022 - Nuriasari, Selvia; Taruno, Agus; Rahmawati, Rahmawati; Rodoni, Ahmad; Pratiwi, Leni Nur (Journal of Applied Islamic Economics and Finance, 2023)
The profit-sharing financing investment ratio is used to measure the results of sharia bank investments in profit sharing based financing. It is known that from 2018 to 2020 the development of assets and disbursed financing (PYD) tended to decrease and the following year it increased, which had an impact on fluctuations in the financing investment ratio. The fluctuation of investment ratios is an interesting problem to research. This research is a quantitative descriptive study that describes the results using numbers with secondary data sources including the OJK Report on Sharia Banking Statistics for 2018 – 2022 and the Monthly Financial Report of Sharia Banks. The research conclusion is that the investment ratio from 2018 to 2022 fluctuates due to the decline in mudharabah financing and musyarakah financing at Sharia Banks.